Profil Penderita Kondiloma Akuminata Di Poliklinik Kulit Dan Kelamin Rumah Sakit Pertamina Bintang Amin Periode Januari 2016 Sampai Desember 2019 - Arif Effendi; Ratna Purwaningrum; Muhammad Syafei Hamzah; Aland Maulana (Universitas Malahayati, 2021)
ABSTRACT: PROFILE OF CONDYLOMA AKUMINATA PATIENTS IN THE SKIN AND SEX POLYCLINIC OF PERTAMINA BINTANG AMIN HOSPITAL FOR THE PERIOD OF JANUARY 2016 TO DECEMBER 2019. Introduction: Sexually transmitted infection (STI) is one of the diseases and causes of health, social and economic problems in many countries. According to WHO, more than 1 million sexually transmitted infections are acquired every day in various parts of the world and more than 290 million women have human papillomavirus infection. In America, data from the CDC shows new cases with more than 19.7 million sexually transmitted infections each year, and about 14.1 million cases are human papillomavirus infections. Objective: This study aims to find out information about the profile of condyloma acuminata sufferers at the Dermatology and Venereology Polyclinic at Pertamina Bintang Amin Hospital for the period January 2016 to December 2019.Methods: This study used quantitative descriptive analysis with the aim of knowing the profile of patients with condyloma acuminata. Sampling was done by using the total sampling method. The sample in this study were patients with condyloma acuminata who were treated at the Dermatology and Venereology Polyclinic at Pertamina Bintang Amin Hospital for the period January 2016 to December 2019 totaling 22 patient medical records. Results: It was found that patients with condyloma acuminata were more commonly found in the age group of 26 to 35 years (early adulthood), as many as 9 patients (40.9) in the female sex, namely 17 patients (77.3%) with married status. as many as 17 patients (77.3) while based on the management of patients more were given treatment using electric surgery, namely as many as 8 patients (36.4%).Conclusion: Patients with condyloma acuminata in order to maintain their health condition, and avoid risk factors that can increase the occurrence of condyloma acuminata, it is hoped that health workers can hold health promotion activities about the prevention of sexually transmitted diseases, especially condyloma acuminata and this research can be used as additional information to develop further research regarding the factors that have not been studied in this study Keywords: Condyloma acuminata, sexually transmitted infection, HPV